The Use of Project Management to Provide Technological Sovereig - O. V. Sysoeva; A. V. Vasina (Вестник Российского экономического университета имени Г. В. Плеханова)
The most important factors, which stipulate the development of any state, are the level of technological independence and availability of sustainable competitive advantages in innovation sphere. Achievement of technological sovereignty in the Russian Federation is a priority task, whose topicality in conditions of unprecedented sanctions pressure is self-evident. In the research the authors analyzed works by home and overseas experts in the field of technological sovereignty and described the problem of possible damage to ecology and human life in the process of developing the technological sphere. Proceed from it the authors put forward an assumption about the necessity of complex approach to reaching the level of critical and end-to-end technologies with regard to goals of sustainable development on the basis of project management. Findings of the research show that there is a certain mutual conformity of goals of sustainable development and national projects being implemented. However, today we have not got projects, whose goals combine achievements of technological independence and principles of sustainable development of the country. The article provides a conceptual scheme of project management use elaborated by the authors. Academic novelty of the scheme is demonstrated by complementarity of specific goals of technological sovereignty and principles of sustainable development.